2021
DOI: 10.1093/ejcts/ezab140
|View full text |Cite
|
Sign up to set email alerts
|

Differences in life expectancy between men and women after aortic valve replacement

Abstract: OBJECTIVES Some researchers have observed an increased number of deaths during the follow-up of young patients who undergo aortic valve replacement due to severe aortic stenosis, suggesting that this procedure does not restore their life expectancy. Our goal was to confirm these findings and explore sex-based differences. METHODS All patients between 50 and 65 years of age who underwent isolated aortic valve replacement in 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Sex differences in survival following surgical aortic valve replacement after propensity score matching in the multicenter spanish aortic valve registry. 61 IPW-HR indicates inverse-probability weighted hazard ratio; PASP, pulmonary artery systolic pressure; and TAVR, transcatheter aortic valve replacement.…”
Section: Av Disordersmentioning
confidence: 99%
See 3 more Smart Citations
“…Sex differences in survival following surgical aortic valve replacement after propensity score matching in the multicenter spanish aortic valve registry. 61 IPW-HR indicates inverse-probability weighted hazard ratio; PASP, pulmonary artery systolic pressure; and TAVR, transcatheter aortic valve replacement.…”
Section: Av Disordersmentioning
confidence: 99%
“…Among the compassionate use or early feasibility trials, [144][145][146] women make up 53% to 66% of enrolled patients highlighting the sex differences in prevalence of the disease in this elderly population. 17 Women are diagnosed with significant TR at an older age compared with men (72 [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] years versus 70 [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] years; P=0.003) and the TR cause in women was more often isolated or related to left-sided VHD, whereas men more often had LV dysfunction related TR. 124 After propensity score matching, there was no sex difference in outcomes, however, TR causes remained significantly associated with all-cause mortality with left valvular disease or LV dysfunction related TR had lower survival compared with patients with primary TR (P=0.004 and P=0.019, respectively).…”
Section: Percutaneous Treatment Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two large multicentre trials have addressed male–female differences in the past [ 27 , 28 ]. In the study of Glaser et al [ 27 ], long-term survival up to 19 years of follow-up is depicted and shown to be great in overall after SAVR; we further expand upon those data and show survival data of up to 30 years of follow-up post-SAVR.…”
Section: Discussionmentioning
confidence: 99%